2016
DOI: 10.3109/01443615.2016.1148126
|View full text |Cite
|
Sign up to set email alerts
|

Intrapartum, postpartum characteristics and early neonatal outcomes of idiopathic polyhydramnios

Abstract: This paper investigates the effect of idiopathic polyhydramnios on the intrapartum and postpartum characteristics of labour and early neonatal outcomes. In this study, intrapartum and early neonatal outcomes of 207 women with idiopathic polyhydramnios and 336 matched healthy pregnant patients were evaluated. In the case of idiopathic polyhydramnios, the active phase of labour became longer when compared to the control group (5.76 ± 3.56 h vs. 4.38 ± 2.8 h, p: 001). The risk of preterm birth (OR 5.23; 95% CI: 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…High rates of maternal and neonatal complications are reported in pregnancies diagnosed with polyhydramnios [ 2 , 5 , 9 ]; however, there are contrasting results regarding maternal and neonatal outcomes when polyhydramnios is idiopathic [ 2 , 5 , 10 , 11 ]. For example, Lallar et al [ 12 ] reported high rates of maternal and perinatal complications of idiopathic polyhydramnios.…”
Section: Introductionmentioning
confidence: 99%
“…High rates of maternal and neonatal complications are reported in pregnancies diagnosed with polyhydramnios [ 2 , 5 , 9 ]; however, there are contrasting results regarding maternal and neonatal outcomes when polyhydramnios is idiopathic [ 2 , 5 , 10 , 11 ]. For example, Lallar et al [ 12 ] reported high rates of maternal and perinatal complications of idiopathic polyhydramnios.…”
Section: Introductionmentioning
confidence: 99%
“…Data regarding early neonatal complications from idiopathic polyhydramnios are conflicting. Some studies have found higher rate of newborn resuscitation with idiopathic polyhydramnios [20]. However, Panting-Kemp et al showed that idiopathic polyhydramnios is unassociated with low 5-min Apgar score [21].…”
Section: Discussionmentioning
confidence: 99%
“…However, in ap proximately 40-50 % of cases, there is no defined risk factor, which is defined as idiopathic or isolated polyhydramnios [4]. Poly hydramnios is associated with adverse maternal and neonatal out comes [5]. If associated with other fetal abnormalities and or with unsatisfactory fetal heart views during routine fetal examinations, polyhydramnios requires a detailed fetal echocardiography as re commended by some of the most eminent scientific societies [6].…”
Section: Introductionmentioning
confidence: 99%